MENINGKATKAN KETERAMPILAN MENYELESAIKAN KERTAS KERJA AKUNTANSI PERUSAHAAN JASA MELALUI MODEL EXPLICIT INSTRUCTION DENGAN PENUGASAN PADA SISWA KELAS XI IPS 1 SMA NEGERI 7 BARABAI TAHUN PELAJARAN 2013/2014 - Syahminiwati Syahminiwati (JURNAL SOCIUS, 2014)
The research was prompted by the situation in which an Accounting course often considered as a hard and difficult course to comprehend by the students. Therefore, the students felt terrified when it comes to the course. This research aimed to improve the skills of students in completing accounting paper work of a service company through explicit instruction model with assignments for grade XI Social Science at SMAN 7 BarabaiYear 2013/2014. The research results showed that in classical mastery learning (completeness of the study)on the cycle had 1 % out of 75.45%, which showed better results than having no explicit instruction with assignment. Unfortunately, the mastery learning of the students was not completely succeeded as it did not reach 80% of the mastery learning. Meanwhile, the result of cycle 2showed that the mastery learning of the students increased in the rate of 90%. The students' response to this model could be seen when they were doing the assignment given, they were enthusiastic and capable to construct with their own understanding, as well as finding a solution of problems they had.Key Words : Explicit Instruction, Accounting, and Working Papers